Stereoselective Monoamine Oxidase‐Catalyzed Oxidative Aza‐Friedel–Crafts Reactions of meso‐Pyrrolidines in Aqueous Buffer. Issue 10 (13th April 2016) - de Graaff, Corien; Oppelaar, Barry; Péruch, Olivier; Vande Velde, Christophe M. L.; Bechi, Beatrice; Turner, Nicholas J.; Ruijter, Eelco; Orru, Romano V. A.
Abstract: We disclose the highly diastereoselective combination of monoamine oxidase‐catalyzed oxidation of meso ‐pyrrolidines and aza‐Friedel–Crafts reactions in aqueous buffer to give valuable enantioenriched 2‐substituted pyrrolidines in a formal double CH activation process. A range of secondary as well as tertiary amines were shown to be suitable substrates for the biocatalytic oxidation and subsequent addition of a variety of C‐nucleophiles. Abstract :